PROFIL KEMAMPUAN LITERASI MATEMATIKA SISWA BERDASARKAN GAYA KOGNITIF - Nok Izatul Yazidah; Nurhasanah Nurhasanah; Nisvu Nanda Saputra (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This type of research used is descriptive research with a qualitative approach because the purpose of this study was to describe the profile of students ' mathematical literacy abilities based on cognitive style. This research was conducted at SMA Dr. Soetomo Surabaya in the 2022/2023 academik year. The subjects of this study were four students of X-MIPA 1 grade, namely one male FI student, one female FI student, one male FD student, and one female FD student. The research instrument was a test of students’ mathematical literacy based on PISA indicators. Mathematical literacy indicators are based on six levels of students’ mathematical literacy. Based on the analysis of the data on the results of the mathematical literacy test, it was obtained a profile description of the mathematical literacy ability of Dr. Soetomo High School namely (1) independent field students are able to work effectively with models in concrete but complex situation, present different information and relate it to real situation. Meanwhile (2) field dependent students are able to carry out the procedures well and choose and apply simple problem solving strategies and can interprete and represent situations.